A Pattern Analysis of Gene Conversion Literature. (27th December 2009) - Lawson, Mark J.; Jiao, Jian; Fan, Weiguo; Zhang, Liqing
Abstract : Gene conversion is an important biological process that involves the transfer of genetic (sequence) information from one gene to another. This can have a variety of effects on an organism, both short-term and long-term and both positive and detrimental. In an effort to better understand this process, we searched through over 3, 000 abstracts that contain research on gene conversions, tagging the important data and performing an analysis on what we extract. Through this we established trends that give a better insight into gene conversion research and genetic research in general. Our results show the importance of the process and the importance of continuing gene conversion research.